The association of Chlamydia trachomatis and Mycoplasma genitalium infection with the vaginal metabolome - Borgogna, Joanna-Lynn C. (Sci Rep, 2020)
Chlamydia trachomatis (CT) and Mycoplasma genitalium (MG) are two highly prevalent bacterial sexually transmitted infections (STIs) with a significant rate of co-infection in some populations. Vaginal metabolites are influenced by resident vaginal microbiota, affect susceptibility to sexually transmitted infections (STIs), and may impact local inflammation and patient symptoms. Examining the vaginal metabolome in the context of CT mono (CT+) and CT/MG co-infection (CT+/MG+) may identify biomarkers for infection or provide new insights into disease etiology and pathogenesis. Yet, the vaginal metabolome in the setting of CT infection is understudied and the composition of the vaginal metabolome in CT/MG co-infected women is unknown. Therefore, in this analysis, we used an untargeted metabolomic approach combined with 16S rRNA gene amplicon sequencing to characterize the vaginal microbiota and metabolomes of CT+, CT+/MG+, and uninfected women. We found that CT+ and CT+/MG+ women had distinct vaginal metabolomic profiles as compared to uninfected women both before and after adjustment for the vaginal microbiota. This study provides important foundational data documenting differences in the vaginal metabolome between CT+, CT+/MG+ and uninfected women. These data may guide future mechanistic studies that seek to provide insight into the pathogenesis of CT and CT/MG infections.